Acute Poisoning of Benzodiazepines Among Patients Admitted to Loghman Hakim Hospital - Mahdavinejad, Arezou; H Shirazi, Farshad; Shadnia, Shahin (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Benzodiazepines have been highly prescribed by physicians and have attracted public attention due to their high safety. These drugs have sedative, hypnotic, anti-anxiety, and anti-seizure properties. However, these drugs are also widely used for suicide. The present study was designed and implemented to determine the distribution of patients poisoned with benzodiazepines in terms of clinical and demographic characteristics. Methods: Investigation of poisoning with benzodiazepines in one year in the poisoning department of Loghman Medical Center in Tehran City, Iran, was carried out as a descriptive-prospective study. In this research, 458 poisoned patients were studied to collect data on their age, gender, drug dosage, type of drug, duration of hospitalization, blood analysis results, and mortality. Results: The majority of patients poisoned with benzodiazepines were women (62.2%). The mean age of people was 31.67 years. The most frequently used drugs were clonazepam and alprazolam. Other drugs used with benzodiazepines were propranolol, methadone, and acetaminophen. The death rate was 1.7%. The incidence of hypoglycemia and creatinine above 1.3 was 8.53% and 11.3%, respectively. Hyperglycemia was 10.6%. There were 11, 80, and 178 cases of elevated alanine transaminase, aspartate aminotransferase, and alkaline phosphatase, respectively. Conclusion: Benzodiazepines have the potential to cause liver and kidney damage and changes in insulin secretion and blood sugar. This issue should be considered when dealing with a poisoned patient to prevent serious injuries.